Analysis of the Impact of Role Models of Islamic Higher Education Alumni on Changes in the Religious Attitudes and Behaviors of the Community in Practicing Islamic Teachings in Monta District - Salmin Salmin; Ilham Ilham; Muslimin Muslimin; Luthfiyah Luthfiyah (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2026)
This research aims to examine in depth the influence of alumni of Islamic Higher Education Institutions (PTAI) as role models on the transformation of religious attitudes and behaviors of the community in implementing Islamic teachings in Monta District, Bima Regency. PTAI alumni occupy a strategic position as agents of socio-religious change, given their capacity in Islamic scholarship, their internalized moral integrity, and their active involvement in education, da'wah, public service, and community development at the grassroots level. This study employs a qualitative approach with a field study design. Data were collected through in-depth interviews, participatory observation, and documentation, involving PTAI alumni and community members as subjects of socio-religious interaction. The findings indicate that PTAI alumni play a significant role as uswah hasanah (good role models) in shaping and guiding the community's religious attitudes and behaviors. This exemplary role is manifested through consistent worship, the application of social morality, and the practice of muamalah values in daily life. The impacts identified include increased religious awareness and worship quality, greater community participation in religious activities, stronger internalization of noble moral values, and the development of a more moderate, tolerant, and contextual pattern of religiosity. However, the effectiveness of PTAI alumni's role is strongly influenced by the intensity of social interaction, the continuity of exemplary conduct, and the support of social and institutional structures that sustain the process of religious development within the community. This study emphasises that the exemplary conduct of PTAI alumni constitutes an effective and sustainable cultural strategy for internalising Islamic values amid the dynamics of social life. Theoretically, these findings contribute to the enrichment of the scholarly discourse in Islamic Religious Education and the sociology of religion, particularly in strengthening the understanding of uswah hasanah as an instrument of socio-religious transformation. Practically, this study provides strategic implications for strengthening the role of PTAI alumni and for formulating community development policies based on Islamic values oriented toward the principle of rahmatan lil ‘alamin.